Exploring the use of Workshops for Educator Support Development - Kirsten, Adolph (The IIE, 2017)
This research aims to explore how the use of workshops can support and develop lecturers to manage and support at-risk students identified in a Higher Certificate programme at a private higher education institution. A quantitative research approach is applied within a post-positivism paradigm. The survey design applicable is cross-sectional survey design and the data collection method is group administration of questionnaires. The target population consists of selected lecturers teaching on a Higher Certificate level. Six respondents participated in this study and each completed the questionnaire consisting of fifteen questions. The analysis of the data obtained from the questionnaires confirms the importance of these workshops for educator support development. This is supported through the findings which indicate that the key goals and objectives of the workshop have been achieved and that the lecturers that have participated are now better equipped to manage and support at-risk students.
Keywords: At-risk students; Training interventions; Workshops; Lecturer development; Lecturer support